The Devil's in the Diversity: Divergent Parasite Faunas and their Impacts on Body Condition in Two Greenland Caribou Populations - Steele, Jillian Felise (Graduate Studies, 2013)
Parasites are important components of ecosystems; significantly impacting host health, and informing on contemporary and historical host movements and environmental changes. I characterised gastrointestinal parasite faunas and assessed their associations to body condition and fecundity in two populations of west Greenland caribou (Rangifer tarandus groenlandicus). Parasite diversity was described using fecal flotations and examinations of abomasa and small intestines. Anoplocephalidae, Nematodirinae and “Strongyle”-type eggs and Eimeria oocysts were found in fecal samples from both populations, but Marshallagia spp. eggs were only found in those from Kangerlussuaq-Sisimiut. Adult nematodes were recovered from all abomasa, with Marshallagia marshalli and Teladorsagia boreoarcticus from Kangerlussuaq- Sisimiut and Ostertagia gruehneri from Akia-Maniitsoq caribou. I hypothesise these faunas were structured by parasite loss during caribou colonization and subsequent parasite spill-over from introduced muskoxen and reindeer. Body condition of caribou from both populations was negatively associated with adult nematode intensity; however, fecundity was only associated with O. gruehneri. 2 years